2011
DOI: 10.1128/jcm.02544-10
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Sequence Typing Implicates Rodents as the Main Reservoir Host of Human-Pathogenic Borrelia garinii in Japan

Abstract: Multilocus sequence typing of Borrelia garinii isolates from humans and comparison with rodent and tick isolates were performed. Fifty-nine isolates were divided into two phylogenetic groups, and an association was detected between clinical and rodent isolates, suggesting that, in Japan, human-pathogenic B. garinii comes from rodents via ticks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 28 publications
4
31
0
1
Order By: Relevance
“…This may suggest that infectivity in C3H/HeN mice differed among the strains. Recently, MLST analysis [20,43] revealed that some pathogenic B. garinii strains made a cluster, and these strains were clearly distinguishable from other B. garinii strains. The MLST type of noninfectious strains was different from the MLST type of infectious strains (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This may suggest that infectivity in C3H/HeN mice differed among the strains. Recently, MLST analysis [20,43] revealed that some pathogenic B. garinii strains made a cluster, and these strains were clearly distinguishable from other B. garinii strains. The MLST type of noninfectious strains was different from the MLST type of infectious strains (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Because rodents have been implicated as the most important reservoirs of B. garinii and B. afzelii, which are the pathogens of human Lyme disease in Japan (Nakao et al 1994, Takano et al 2011, and B. miyamotoi, which shares the same vector, we hypothesized that they share the same reservoirs. Therefore, we compared infection rates of B. miyamotoi among wild rodents trapped in Hokkaido, Japan, to the more studied B. garinii and B. afzelii.…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic analysis was conducted using maximum-likelihood (Tamura et al, 2011). Consistent with previous analyses (Margos et al, 2009;Scholz et al, 2013;Takano et al, 2011), European and Asian B. bavariensis sp. nov. formed a sister clade to B. garinii In this context, it is important to emphasize that giving species status to ecotypes of bacteria that form phylogenetically divergent sequence clusters (Koeppel et al, 2008) would have the advantage of being ecologically, epidemiologically and clinically predictive.…”
mentioning
confidence: 97%
“…This typing scheme is based on eight chromosomally located housekeeping genes, clpA, clpX, nifS, pepX, pyrG, recG, rplB and uvrA (Margos et al, 2008). We also included in our analyses sequence types (STs) of the following previously typed strains using the same MLSA scheme: (i) strains found in Ixodes persulcatus ticks in Mongolia (Scholz et al, 2013); (ii) NT29-like strains from Asia of rodent, tick and human origin which have been described by Takano et al (2011); or (iii) strains which were deposited in the MLST database (borrelia.mlst.net; Table 2). …”
mentioning
confidence: 99%